2022
DOI: 10.1007/s10953-022-01214-7
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Temperature Dependence of the Octanol–Air Partition Ratio: A New Model for Estimating $$\Delta {U^{ \circ}_{\text{OA}}}$$

Abstract: The octanol–air partition ratio (KOA) describes the partitioning of a chemical between air and octanol and is often used to approximate other partitioning phenomena in environmental chemistry (e.g., blood–air, atmospheric particulate matter–air, polyurethane foam-air). Such partitioning processes often occur at environmental temperatures other than 25 °C. Enthalpies $$\Delta {H^{ \circ}_{\text{OA}}}$$ Δ H OA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…A similar observation was noted for Chukar partridge for thresholds derived from G R values measured at low (K OA@25 = 10 4.72 ) and high (K OA@25 = 10 5. 19 ) elevations. Additionally, thresholds calculated for flying birds were higher on average (log K OA@25 = 6.17 ± 0.25) than those calculated for the same species at rest (log K OA@25 = 5.28 ± 0.35).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar observation was noted for Chukar partridge for thresholds derived from G R values measured at low (K OA@25 = 10 4.72 ) and high (K OA@25 = 10 5. 19 ) elevations. Additionally, thresholds calculated for flying birds were higher on average (log K OA@25 = 6.17 ± 0.25) than those calculated for the same species at rest (log K OA@25 = 5.28 ± 0.35).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In general, reptiles had lower reported G R values compared to those of mammals and birds (Figure S2 and Appendix S2). Because K OA is dependent on temperature, , we calculated K OA@25 from individual G R values reported across a range of different temperatures, which often included several measurements for the same species [ n = 86 observations (Appendix S4)]. Most of the reptile G R measurements [64% ( n = 50)] were reported at T B > 25 °C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the reported K OA values for fluorotelomer alcohols by Goss et al 12 and Thuens et al 13 are inconsistent with each other, and regressions on the reported log K OA values against reciprocal temperature show poor linearity. 15 These measurements were presumably made with the plateau method and involved large volumes of air passing through the generator column. While it is assumed that the octanol concentrations at the end of the column during these experiments remain constant, 13,14 the octanol concentration was not measured after column preparation, and it is possible that the octanol concentrations within that column may have declined significantly during the measurements.…”
Section: ■ Introductionmentioning
confidence: 99%
“…27,28 The ΔU°O A value was estimated from the estimated K OA at 25 °C using a simple correlation equation. 15…”
Section: ■ Introductionmentioning
confidence: 99%